Environmentally Benign Transamidation Protocol for Weakly Nucleophilic Aromatic Amines with N‐Acyl‐2‐piperidinones: Catalyst‐, Additive‐, Base‐ and Solvent‐Free Condition. Issue 9 (18th August 2022) - Rajan, Ida Angel Priya Samuel; Subramani, Muthuraman; Pushparathinam, Gopinath; Rajendran, Saravanakumar
Abstract: Transamidation of weakly nucleophilic aromatic amines is achieved under melt conditions and in absence of catalyst, activating agent, base, and solvent. Chemoselectivity of the protocol is demonstrated with transamidation of aniline‐bearing protic carboxylic acid group and wide range of anilines. Broad applicability of the process is demonstrated with the synthesis of bioactive natural product amide, Avenanthranamide‐A. By‐product was isolated for re‐use in synthesis of starting amide, manifests atom economy, and sustainability of the protocol. Thus, our findings imply that the developed protocol is environmentally benign, operationally simple yet versatile for protection‐deprotection free synthesis of amides, peptides and amide‐based drugs. Abstract : Transamidation of N ‐acyl‐2‐piperidinone with weakly nucleophilic aromatic amines is achieved under melt conditions and in absence of catalyst, activating agent, base, and solvent. Chemoselectivity of the protocol is demonstrated with transamidation of aniline‐bearing protic carboxylic acid group and wide range of anilines.